Raman Spectroscopic Analysis of an Early 20th Century English Painted Organ Case by Temple Moore - Christopher Brooke; Howell Edwards; Peter Vandenabeele; Sylvia Lycke; Michelle Pepper (Heritage, 2020)
An organ case from Lincoln, England, designed by the architect Temple Moore in 1907 was examined during conservation work using Raman spectroscopy in order to analyze the decorative paint composition. Samples from the six principal colours were extracted and examined using a Bruker Senterra R200-L spectrometer. The results are the first known formal analysis of a painted scheme by this architect, and they reveal a mixture of commonly used pigments for the period and the unexpected use of simpler, earth pigments, along with an unusual admixture in the red, along with an organic additive. The findings are of importance to both the conservation of Temple Moore’s artwork, in understanding the experimentation used in early twentieth-century England, and in furthering our knowledge of ecclesiastical decorative artwork of the late nineteenth and early twentieth centuries.